2012
DOI: 10.1371/journal.pone.0051196
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Heat Shock Response of Salmonella Typhimurium Shows Hysteresis and Heated Cells Show Increased Resistance to Heat and Acid Stress

Abstract: We investigated if the transcriptional response of Salmonella Typhimurium to temperature and acid variations was hysteretic, i.e. whether the transcriptional regulation caused by environmental stimuli showed memory and remained after the stimuli ceased. The transcriptional activity of non-replicating stationary phase cells of S. Typhimurium caused by the exposure to 45°C and to pH 5 for 30 min was monitored by microarray hybridizations at the end of the treatment period as well as immediately and 30 minutes af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…They found that acidification changed the transcriptional levels of only a few genes, while heat stress caused widespread transcriptional changes (49). They also found that 85% of the genes upregulated by heat shock remained upregulated 30 min after the reversal to 25°C and that this was associated with increased tolerance to further heat stress or acidification (49). This agrees with our results, which also found global transcriptional changes after heat shock.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…They found that acidification changed the transcriptional levels of only a few genes, while heat stress caused widespread transcriptional changes (49). They also found that 85% of the genes upregulated by heat shock remained upregulated 30 min after the reversal to 25°C and that this was associated with increased tolerance to further heat stress or acidification (49). This agrees with our results, which also found global transcriptional changes after heat shock.…”
Section: Discussionsupporting
confidence: 91%
“…Several recent studies have investigated the transcriptional response of S. enterica to stress. Pin et al exposed Salmonella Typhimurium strain 4/74 stationary-phase cultures to 45°C or pH 5 for 30 min and compared the microarray data from RNA collected (i) during exposure to these conditions, (ii) immediately after reversal to normal conditions, and (iii) at 30 min postreversal with those for control cultures exposed to 25°C and pH 7 (49). They found that acidification changed the transcriptional levels of only a few genes, while heat stress caused widespread transcriptional changes (49).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the transcriptional responses of S. Typhimurium during growth and in response to different environmental stress conditions have also been detailed [7-10], a systematic analysis of how the S. Typhimurium responses interact with each other has not been performed.…”
Section: Introductionmentioning
confidence: 99%